Musculoskeletal Disorders in Dentists: A Systematic Review (Update Dental College Journal, 2018)
Background: Musculoskeletal disorders (MSDs) are the most important occupational health problems particularly in dentists. Technological advancements in the field of dental equipment and material- shave not fully eliminated the musculoskeletal problems of dentists.Methods: This systematic review began with a search of a range of a relevant articles from May to July 2017 in Google Scholar with the key words musculoskeletal disorders, dental practitioners, dentist, risk factors. According to the inclusion and exclusion criteria of the manuscript a total 13 origi- nal articles were included for this review work.Results : This review work observed the highest overall prevalence of MSDs among dental practition- ers were 92% with the most prevalent regions for pain in dentists have been shown to be the neck (41-75.7%), lower back (35–73.5 %) and shoulder (29–43.3%). Different risk factors have been identi- fied, including inadequate postures, long working hours without pause, direct inspection, physical load, repetitive movements etc.Conclusion: Overall, the review emphasizes that MSDs represent a significant burden for the dental professionals. Further studies are required including large sample size to be able to reach valid conclusion and be able to generalize results.Update Dent. Coll. j: 2017; 7 (2): 38-42